Comparative Study on Mechanical Properties and Microstructure of Binary Aluminium Alloy using Sand and Green Sand Molds - Mohd Ichwan, Nasution, Ir. (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.